2016
DOI: 10.1186/s13256-016-0856-0
|View full text |Cite
|
Sign up to set email alerts
|

Sternoclavicular joint septic arthritis with chest wall abscess in a healthy adult: a case report

Abstract: BackgroundSeptic arthritis of the sternoclavicular joint is rare. It can be associated with serious complications such as osteomyelitis, chest wall abscess, and mediastinitis. In this report, we describe a case of an otherwise healthy adult with septic arthritis of the sternoclavicular joint with chest wall abscess.Case presentationA 68-year-old Japanese man presented to our hospital complaining of pain and erythema near the right sternoclavicular joint. Despite 1 week of oral antibiotics, his symptoms did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…Abscess specifically was found about 20% of the time; however, the majority were located in the chest wall. 11 Similarly, Akkasilpa et al 12 found that retrosternal abscesses developed in 28% of patients from SCJ septic arthritis. A cervical abscess is exceedingly rare with our case being the second reported.…”
Section: Discussionmentioning
confidence: 94%
“…Abscess specifically was found about 20% of the time; however, the majority were located in the chest wall. 11 Similarly, Akkasilpa et al 12 found that retrosternal abscesses developed in 28% of patients from SCJ septic arthritis. A cervical abscess is exceedingly rare with our case being the second reported.…”
Section: Discussionmentioning
confidence: 94%
“…Imaging supports the diagnosis of sternoclavicular septic arthritis, but the initial plain radiographs are normal in most such patients (3, 6). CT or MRI should be routinely performed in all cases of sternoclavicular joint arthritis (3-7). If life-threatening complications (such as chest wall phlegmon or abscess, retrosternal abscess, mediastinitis, or pleural extension) are observed, joint resection is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Plain radiography may show osteolysis and osteosclerosis in the distal clavicle, but the findings may seem normal initially (3). Because of the limited information that plain radiography provides, the use of magnetic resonance imaging (MRI), computed tomography (CT), and ultrasound may aid in the arrival at a precise diagnosis (3-7). Ultrasound has increasing utility in the diagnosis of musculoskeletal conditions when used by an experienced clinician (6).…”
Section: Introductionmentioning
confidence: 99%
“…Sternoclavicular joint (SCJ) infection is an uncommon condition, accounting for only 0.5 %-1.0 % of all septic arthritis and less than 0.5 % of septic arthritis in healthy patients (Tanaka et al, 2016). Several risk factors have been associated with SCJ infection, including intravenous drug use, concomitant infection at a different location, diabetes mellitus, trauma, and central venous line-related infection.…”
Section: Introductionmentioning
confidence: 99%